Who pays the greenium and why? A decomposition - Daniel Fricke; Christoph Meinerding (Deutsche Bundesbank, 2024)
The average yield differential between a green and a matched conventional bond ("greenium") amounts to minus 3 basis points. We decompose this greenium along the bonds' ownership structure and document that investment funds, banks and insurance companies pay most of it. Dissecting further, the greenium paid by investment funds (and their clients) is mostly explained by an average level effect, confirming the narrative that these investors have non-pecuniary sustainability preferences. The greenium paid by banks is markedly different and cannot be explained by such preferences. Rather banks overweight specific green bonds with a sizeable greenium, pointing towards an interaction between the greenium and bank-related financial frictions.
Keywords: G11; Q01; 330; Green bonds; sustainable investment; greenium; ownership structure; securities holdings